Housing demand shocks, foreign labour inflows and consumption - William Gatt; Germano Ruisi (Central Bank of Malta, 2020)
In this paper we propose a SVAR identification strategy to disentangle two housing demand shocks and their ensuing effect on consumption. This builds on the literature studying the role of the collateral and housing wealth effects on household behaviour. A mix of zero and sign restrictions allows us to disentangle domestic and foreign housing demand shocks, which capture different motivations for owning or using real estate by residents and foreign workers respectively. Using Maltese data over the period 2000Q1-2019Q4 we find that both housing demand shocks generate an increase in consumption, in line with the theoretical predictions from microfounded models with financial frictions. While a domestic housing demand shock drives consumption via both the collateral and housing wealth channels, a foreign housing demand shock operates mainly via the latter. Moreover, these shocks account for about 40% of the fluctuations in house prices and consumption in the long run. We show that from a historical perspective they match well with the dynamics of foreign worker growth and a selection of events that are associated with activity in the housing market.
Keywords: C11; C32; G51; R21; 330; house prices; housing wealth; collateral; identification; SVAR